SISTEM INFORMASI PENEMPATAN KERJA MENGGUNAKAN CASE BASED REASONING (STUDI KASUS PADA ALUMNI STIKI MALANG) - Sakaria, Setiabudi; Favian, Joshua Adriel (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2014)
The development of information technology has brought many advances and benefits that we enjoy today. It is inseparable from the development of computers that enable people to make decisions . The computer can receive and process the data into critical information needed to make decisions . One example is the decision-making in determining which placement STIKI Alumni who have graduated in accordance with the study program and its competence . During the election of alumni STIKI not work according to your interests and talents as well as its competence , requiring rapid decision-making system in helping job placement that suits them . Case -Based Reasoning is a method used to compare the similarity value of the existing data with new data , so that important information will be elected for rapid decision-making and tepat.Oleh because it needed a job placement system using Case -Based Reasoning online so it can determine for alumni who would find a job to work on the job position and the company that is in the database that have been stored previouslyKeywords :Job placement system, Case Based Reasoning